The Effectiveness of Anti-R. equi Hyperimmune Plasma against R. equi Challenge in Thoroughbred Arabian Foals of Mares Vaccinated with R. equi Vaccine. (3rd April 2014) - Erganis, Osman; Sayin, Zafer; Hadimli, Hasan Huseyin; Sakmanoglu, Asli; Pinarkara, Yasemin; Ozdemir, Ozgur; Maden, Mehmet
Abstract : This study aimed to determine the effectiveness of a pregnant mare immunization of a Rhodococcus equi ( R. equi ) vaccine candidate containing a water-based nanoparticle mineral oil adjuvanted (Montanide IMS 3012) inactive bacterin and virulence-associated protein A (VapA), as well as the administration of anti- R. equi hyperimmune (HI) plasma against R. equi challenge in the mares' foals. The efficacy of passive immunizations (colostral passive immunity by mare vaccination and artificial passive immunity by HI plasma administration) was evaluated based on clinical signs, complete blood count, blood gas analysis, serological response (ELISA), interleukin-4 (IL-4) and interferon gamma (IFN- γ ), total cell count of the bronchoalveolar lavage fluids (BALF) samples, reisolation rate of R. equi from BALF samples (CFU/mL), lung samples (CFU/gr), and lesion scores of the organs and tissue according to pathological findings after necropsy in the foals. The vaccination of pregnant mares and HI plasma administration in the foals reduced the severity of R. equi pneumonia and lesion scores of the organs and tissue by 3.54-fold compared to the control foals. This study thus indicates that immunization of pregnant mares with R. equi vaccine candidate and administration of HI plasma in mares' foals effectively protect foals against R. equi challenge.